Evaluation of Salivary Lactate Dehydrogenase as a Prognostic Biomarker in Tobacco Users with and without Potentially Malignant Disorders of the Oral Cavity - Javaraiah, Rashmi Kademadkal; David, Chaya Manoranjini; Namitha, J.; Tiwari, Ritu; Benakanal, Prabhavati (South Asian Journal of Cancer, 2020)
Background Oral squamous cell carcinoma (OSCC) is a deadly disease that develops in a multistage process and is often preceded by oral potentially malignant disorders (PMDs), of which many are caused by tobacco usage. It is associated with a shift from an aerobic to anaerobic glycolytic pathway, and hence an increase in lactate dehydrogenase (LDH) levels is seen. The objective of this study was to estimate and correlate the level of salivary LDH in healthy individuals with tobacco users (with or without PMDs).Methods A total of 78 patients were selected from the Department of Oral Medicine and Radiology, Dayananda Sagar College of Dental Sciences, Bengaluru, Karnataka, India, and were divided into three groups of 26 patients each, namely controls, tobacco users without PMD, and tobacco users with PMD. A total of 1 mL of unstimulated saliva was collected from each patient using the spit method. Sample was subjected to centrifugation at 2,500 rpm, and salivary LDH was quantified by a standard kit (LDH-P kit, DIALAB, Neudorf, Austria) using an autoanalyzer.Results There was a statistically significant (p < 0.001) gradual increase in the level of LDH in controls (267 ± 27.64 U/L), tobacco users without PMD (391 ± 80.53 U/L), and tobacco users with PMD (706.1 ± 199 U/L). Increase in the LDH level was also noted with increased duration and frequency of the habit.Conclusion LDH can potentially be used as a promising biomarker in the very early stages of progression toward oral cancer caused by tobacco use.
Keywords: lactate dehydrogenase; oral cancer; prognosis; saliva; tobacco